Urgency of Fatwa on Domestic Psychological Violence in Indonesia as an Effort to Protect Women's Rights - Nasyiah, Iffaty (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
One that requires a fatwa is domestic psychical violence, which has different interpretations in the two legal systems. The purpose of this study is to analyze the urgency of forming a fatwa regarding psychical violence so that it has clarity on norms that must be guided for Indonesian Muslims This research is juridical-normative research with a conceptual and comparative approach. The results show that the urgency of forming fatwa regarding domestic psychical violence is related to 1. harmonisation between positive law and Islamic law regarding the concept of psychical violence; 2. fatwas have social power and can provide legitimacy and serve as the juridical basis for law enforcement; and 3. In terms of the fatwa of psychical violence as a source of material law, fatwa can be used as a source of material law in constructing a law. Fatwas can provide a solid basis for policymakers and legislators in drafting more formal regulations. This research can be used as discourse material regarding the importance of fatwa on psychical violence in the household. Research can be done by sharpening the differences in interpretation between Islamic law, positive law and customary law.